2017
DOI: 10.11648/j.ajwse.20170301.11
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Levels in Surface and Groundwater in Africa: A Review

Abstract: Abstract:Fluoride has been reported to be among natural pollutant of water in Africa. High fluoride levels beyond the recommended World Health Organization limit of 1.5 mg/l has been observed in various Africa countries. However, the information is scattered in different publication medium. Therefore, objective of this work was to put together the information on fluoride levels in surface and groundwater in Africa, and describe the status and distribution of fluoride in water among African countries. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 29 publications
1
65
1
Order By: Relevance
“…High F groundwater's are well documented in both countries and have been linked to hydrothermal sources (Bath 1980, Reimann et al 2003, Rivett et al 2019. They are also found in high concentrations in other parts of the East African Rift system (Malago et al 2017). Arsenic was not found above the WHO limit of 10 µg l −1 in any HPB in this study, even though As has been reported to be an issue in some other parts of Africa (e.g.…”
Section: Discussioncontrasting
confidence: 47%
“…High F groundwater's are well documented in both countries and have been linked to hydrothermal sources (Bath 1980, Reimann et al 2003, Rivett et al 2019. They are also found in high concentrations in other parts of the East African Rift system (Malago et al 2017). Arsenic was not found above the WHO limit of 10 µg l −1 in any HPB in this study, even though As has been reported to be an issue in some other parts of Africa (e.g.…”
Section: Discussioncontrasting
confidence: 47%
“…Critical exposure ages for development of dental fluorosis are from 1 to 7 years of age during permanent dentition development when excessive fluoride exposure disrupts enamel mineralization, with dental fluorosis externally evident, visually, upon eruption of these permanent teeth. We also asked about water source, as ESCC risk has been linked to consumption of non‐piped water, and in Kenya surface waters have some of the highest fluoride levels worldwide …”
Section: Methodsmentioning
confidence: 99%
“…We also asked about water source, as ESCC risk has been linked to consumption of non-piped water, 22,23 and in Kenya surface waters have some of the highest fluoride levels worldwide. 24 For the present investigation, socioeconomic factors (job, education and amenities), age, ethnicity, alcohol (by type), tobacco (smoking and smokeless), hot beverages, household air pollution, and family history of ESCC represent potential confounders or effect modifiers. Place of birth and of current residence were obtained, and, with the aid of databases of all Kenyan places (www.geonames.org) and their corresponding GPS coordinates, current residence was geocoded to investigate the potential of spatial clustering of dental fluorosis and of selection bias.…”
Section: Oral Health and Other Exposure Variablesmentioning
confidence: 99%
“…In urban areas, contamination is mainly attributed to industrial activities and onsite sanitation (Mjemah et al 2011;Napacho and Manyele 2010;Muzuka 2015, 2016a, b) where as in sub-urban to rural areas it is mainly caused by agriculture activities (Bowell et al 1996;Nkotagu 1996a, b;Bowell et al 1997;Mohammed 2002;Mjemah et al 2011;Napacho and Manyele 2010;Muzuka 2015, 2016a, b). Fluoride is one among the natural contaminants in groundwater systems which are common in volcanic regions of Tanzania (Nanyaro et al 1983;Ghiglieri et al 2010;Malago et al 2017). According to the fluoride groundwater survey in Tanzania, it was found that 30% of waters used for drinking exceed the recommended standard by WHO, 1.5 mg/L (Thole 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to the fluoride groundwater survey in Tanzania, it was found that 30% of waters used for drinking exceed the recommended standard by WHO, 1.5 mg/L (Thole 2013). The most affected zones are the areas along the rift system, the central to Lake zone parts (Malago et al 2017). For instance, along the rift system, Nanyaro et al (1983) reported high concentration of 690 mg/L from Lake Momella (Fig.…”
Section: Introductionmentioning
confidence: 99%